2011
DOI: 10.1155/2011/183937
|View full text |Cite
|
Sign up to set email alerts
|

SystemicBartonella henselaeInfection in Immunocompetent Adult Presenting as Fever of Unknown Origin

Abstract: Systemic clinical presentations of infection caused by Bartonella henselae are rare in immunocompetent adults. We report four cases with hepatic and/or splenic involvement, presenting as fever of unknown origin. We discuss diagnosis and treatment of this infection. Bartonella henselae serology allows an easy diagnosis of hepatosplenic involvement in cat scratch disease, a clinical picture that appears to be underrecognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…31 , 34 Herein, we describe 3 new cases of HS-CSD and review 33 previously reported cases with a focus on clinical descriptions, diagnosis, and therapeutic approaches. 4 , 6 , 9 , 10 , 18 , 23 , 24 , 26 , 27 , 29 , 30 , 33 , 35 , 36 , 38 42 , 44 , 45 …”
Section: Introductionmentioning
confidence: 99%
“…31 , 34 Herein, we describe 3 new cases of HS-CSD and review 33 previously reported cases with a focus on clinical descriptions, diagnosis, and therapeutic approaches. 4 , 6 , 9 , 10 , 18 , 23 , 24 , 26 , 27 , 29 , 30 , 33 , 35 , 36 , 38 42 , 44 , 45 …”
Section: Introductionmentioning
confidence: 99%
“…Infection with one or more Bartonella sp. has also been associated with fever of unknown origin [5-9], and arthritic and neurological disorders [10-12]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, splenic rupture and granulomatous splenitis have been associated with Bartonella sp . infection in people . Also, infection with B. henselae was reported in a man with hypergammaglobulinemia, splenomegaly, and polyclonal plasmacytosis who developed fever and other complications postsplenectomy .…”
Section: Discussionmentioning
confidence: 96%
“…In people, fever often accompanies an acute infection with Bartonella spp . In 1 recent human case series, hepatosplenic B. henselae infection was diagnosed in 4 patients with fever of unknown origin . In addition, cat scratch disease is characterized by a classical triad including a history of a cat scratch, fever, and lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%